ISSUES OF QUALITATIVE EXCESS OF ACCOMPLICES ACCORDING THE CRIMINAL CODE OF THE REPUBLIC OF ARMENIA - Danielyan, Artur (State and Law, 2025)
In criminal law theory, there are two types of excess: quantitative and qualitative. Qualitative excess occurs when the perpetrator commits a crime that is entirely different in nature from the planned crime or engages in a crime other than what was stipulated. The Criminal Code of the Republic of Armenia differentiates between quantitative and qualitative excess by establishing specific rules for criminal liability.However, we believe the Criminal Code should explicitly state that if the perpetrator commits a crime different from the initial arrangement, the other accomplices must be held accountable for their complicity in the crime involved in their intent. Furthermore, in cases where the perpetrator commits a less dangerous crime instead of the agreed-upon offense—either by damaging the intended object or by causing harm to a different object—these scenarios should not be classified as excess. Instead, they fall under the concept of "failed complicity," which is already addressed in the existing regulations of the Criminal Code.Thus, we argue that part 4 of Article 49 of the Criminal Code of the Republic of Armenia unnecessarily complicates the Code, as the provisions for criminal responsibility related to unsuccessful conspiracies are already adequate for assessing these cases.
Keywords: excess; quantitative; qualitative; accomplice; criminal liability; intent; serious crime; failed complicity